2016
DOI: 10.1007/s00784-016-2013-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photon-initiated photoacoustic streaming, passive ultrasonic, and sonic irrigation techniques on dentinal tubule penetration of irrigation solution: a confocal microscopic study

Abstract: The activation of the irrigant and the creation of the streaming with the Er:YAG laser have a positive effect on the irrigant penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 45 publications
4
47
0
1
Order By: Relevance
“…Pilot experiments with fluorescent dyes and methylene blue exhibited advantages for the latter, as dentine shows intense autofluorescence. Penetration depths of methylene blue observed in this study are in line with other findings; comparable studies of sealer penetration after irrigation show similar penetration depths into dentine as well as significantly superior sealer penetration at greater distances from the apex (Akcay et al 2017, Chaudhry et al 2017, Uzunoglu-€ Ozy€ urek et al 2017, Bharti et al 2018. In order to exclude errors during the analysis of penetration depths, the same two examiners performed this task together.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Pilot experiments with fluorescent dyes and methylene blue exhibited advantages for the latter, as dentine shows intense autofluorescence. Penetration depths of methylene blue observed in this study are in line with other findings; comparable studies of sealer penetration after irrigation show similar penetration depths into dentine as well as significantly superior sealer penetration at greater distances from the apex (Akcay et al 2017, Chaudhry et al 2017, Uzunoglu-€ Ozy€ urek et al 2017, Bharti et al 2018. In order to exclude errors during the analysis of penetration depths, the same two examiners performed this task together.…”
Section: Discussionsupporting
confidence: 92%
“…Various designs for this type of study can be found, where fluorescently labelled irrigants (Akcay et al . ) or sealers (Chaudhry et al . , Uzunoglu‐Özyürek et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, while Chaudhry et al (34) found that the use of the EndoActivator significantly increased the sealer penetration compared with conventional irrigation, Generali et al and Bolles et al reported no statistically significant differences (20,22). To our knowledge, there has been only one study in the literature about the efficacy of the EndoActivator on irrigant penetration, and this study showed that the EndoActivator was superior to CI in percentage of irrigation solution penetration (21). The difference in results was most likely due to differences in the study design and the activation protocols used (10).…”
Section: Discussionmentioning
confidence: 65%